IMPLEMENTASI ALUR DIGITALISASI SCANNING DALAM KEGIATAN REKAM MEDIS ELEKTRONIK DI INSTALASI GAWAT DARURAT (IGD) RSUD AL-IHSAN PROVINSI JAWA BARAT - Rahayu, Ayu Hendrati; Ginting, Gerinata; Pitriani, Kania (Jurnal TEDC; Vol 17 No 3 (2023): JURNAL TEDC, 2023)
Digitization of medical records is a process of switching converting medical record document media into digital documents using scanners. Digitization of medical records is one of the supports in implementing electronic medical records. RSUD Al-Ihsan West Java Province has digitized scanning of the medical record files for the Emergency Installation, which began in 2019. The purpose of this study was to determine the implementation of the digitalization scanning flow in electronic medical record activities at the Emergency Installation of RSUD Al-Ihsan, as well as the obstacles and effort in its process.  The research method used is descriptive qualitative method with data collection techniques through observation, interviews and documentation. The subjects in this study were scanning department officers and the object used was the flow of digitizing scanning of medical record files.  The results showed that 16% of activities were not in accordance with the digitization flow. There were obstacles, namely there were no fixed procedures, lack of human resources, it took more time to open the staples, dirty scanners, folded medical record files so the files are difficult to read, the scan results are not connected to the SIMRS and the computer's internal memory storage is limited. The efforts he has made are by making regular procedures, adding human resources, routine maintenance for equipment, and uploading scan results periodically to the SIMRS. Researchers suggest that it is increase research seen from the effectiveness of the workload in the digitalization flow process.